2023
DOI: 10.1002/adhm.202301826
|View full text |Cite
|
Sign up to set email alerts
|

Novel Natural Carrier‐Free Self‐Assembled Nanoparticles for Treatment of Ulcerative Colitis by Balancing Immune Microenvironment and Intestinal Barrier

Shan Gao,
Haocheng Zheng,
Shujing Xu
et al.

Abstract: Ulcerative colitis (UC) is a chronic inflammatory illness affecting the colon and rectum, with current treatment methods being unable to meet the clinical needs of ulcerative colitis patients. Although nanomedicines are recognized as promising anti‐inflammatory medicines, their clinical application is limited by their high cost and unpredictable safety risks. In this study, we reveal that two natural phytochemicals, berberine (BBR) and hesperetin (HST), self‐assemble directly to form binary carrier‐free multi‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Another study revealed that two natural plant compounds, berberine and hesperetin, directly self-assembled into carrier-free dual-function spherical berberine-hesperetin nanoparticles (BBR-HST NPs) through noncovalent bonds such as electrostatic interactions, π–π stacking, and hydrogen bonds. BBR-HST NPs exhibited synergistic anti-inflammatory effects, effectively modulating the immune environment and repairing damaged intestinal barriers, exhibiting significant advantages in the treatment of ulcerative colitis and inflammation as compared to equivalent doses of BBR and HST [ 88 ]. Furthermore, two natural compounds with antimicrobial and anti-inflammatory properties, berberine and sanguinarine, could self-assemble directly into carrier-free binary small molecule berberine-sanguinarine (BA-SAN) hydrogels through noncovalent bonds, such as electrostatic attraction, π–π stacking, and hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that two natural plant compounds, berberine and hesperetin, directly self-assembled into carrier-free dual-function spherical berberine-hesperetin nanoparticles (BBR-HST NPs) through noncovalent bonds such as electrostatic interactions, π–π stacking, and hydrogen bonds. BBR-HST NPs exhibited synergistic anti-inflammatory effects, effectively modulating the immune environment and repairing damaged intestinal barriers, exhibiting significant advantages in the treatment of ulcerative colitis and inflammation as compared to equivalent doses of BBR and HST [ 88 ]. Furthermore, two natural compounds with antimicrobial and anti-inflammatory properties, berberine and sanguinarine, could self-assemble directly into carrier-free binary small molecule berberine-sanguinarine (BA-SAN) hydrogels through noncovalent bonds, such as electrostatic attraction, π–π stacking, and hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%